Beyond adjustment : management of the Nigerian economy - The Nigerian economic society (Ibadan: The Nigerian economic society, 1996)
The volume consists of papers selected according to the unsual careful review process of the society.The papers are broadly divided into four parts- political framework and part two examines the real sector- agriculture, informal sector and industry.
Selected papers for the 1996 Annual Conference.
aia 19/09/2016
Keywords: Structural adjustment; Beyond adjustment; Economic policy; Nigeria